Occurrence of viruses and stunting diseases and estimative of yield losses by mollicutes in corn in Paraná State, Brazil - Oliveira, Elizabeth de; Resende, Renato de Oliveira; Pecci, María de la Paz Giménez; Laguna, Irma Graciela; Herrera, Patricia; Cruz, Ivan (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to evaluate the occurence and yield losses by corn stunting diseases and maize viruses in "safrinha" season. Disease diagnostics based on plant symptoms were confirmed by PCR or RT-PCR assays. Insect samples were collected in 24 fields for identification of vectors of the pathogens. Corn stunting diseases symptoms were observed in all crops evaluated, with incidence levels ranging from 6.2% to 49.9% (average 20.7%) and the presence of the leafhopper Dalbulus maidis, was detected in 20 of the 24 areas evaluated. This insect species was prevalent, representing 66,6% of total leafhoppers specimens collected. The potential yield losses caused by mollicutes was estimated around US$ 16.5 million. Few plants showing Maize rayado fino virus and Maize dwarf mosaic virus symptoms were found and virus infection was confirmed by RT-PCR. Mal de Río Cuarto virus was not detected in all 441 plants analyzed by DAS-ELISA. Results of PCR assays indicated the presence of a possible phytoplasma different from maize bushy stunt phytoplasma in two stunting maize plants showing leaves distortions and grain in the inflorescence. However, new studies should be done to confirm the identity of this possible new phytoplasma.